KOLABORATIF GOVERNANCE DALAM PENANGGULANGAN COVID-19 DI WILAYAH KABUPATEN LINGGA - ZAMRONI, ZAMRONI (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The government has continued to undertake intensive measures to combat COVID-19 since the beginning of March 2020 to lower the pace of COVID-19 spread. Based on preliminary findings, there is a collaborative approach in Lingga Regency that has not been fully utilized, with indications of a lack of material assistance in addressing the needs of facilities and infrastructure from every village in the regency. The goal of this study is to look into "Collaborative Governance in the Lingga Regency in Combating COVID-19." This study used a qualitative method with a descriptive approach as the research method. According to the findings, the Starting Condition is characterized by adequate resources; the Collaborative Process is characterized by an interactive discourse, growing trust, dedication to the process, and mutual understanding; and the End State is characterized by a lack of resources. Facilitative Leadership is characterized by a large number of facilities and infrastructure that may meet current needs but are underutilized; The Lingga Regency administration has done an excellent job with institutional design, which includes participation, the role of external parties, and policy regulations. Meanwhile, financial indications that stymie collaboration, such as the fact that small company aid is not particularly controlled, and public view that there is still suspicion in Covid-19 and a refusal to be vaccinated, can stymie the current partnership process